A evolução genética do HIV-1 entre indivíduos em tratamento antirretroviral - Giron, Leila Bertoni [UNIFESP] (2017)
Abstract Background: Although antiretroviral therapy (ART) suppresses HIV to undetectable levels in plasma, it is unclear if treatment fully suppresses HIV replication. We aimed to determine if current ART is fully suppressive by investigating HIV genetic diversity and divergence during ART as a proxy for ongoing viral residual replication. Methods: Peripheral blood from 34 HIV-infected individuals were evaluated immediately before ART onset and after four years of continuous ART treatment with undetectable viral loads. Ultradeep sequencing (UDS) of the gp41 and C2V3 regions of HIV gp160 was performed. Lowfrequency viral variants were filtered based on an error rate of 0.5% derived from misincorporations in the HIV BAL plasmid, which was amplified and sequenced with the samples. HIV divergence and diversity at each time point were calculated using average pairwise distance. Genetic compartmentalization analyses between time points based on tree topologies and pairwise distance were also performed. Correlations between genetic divergence and elapsed time between sampling points were evaluated using linear regression, implemented using TempEst software (root-to-tip analysis). Results: There was no correlation between read depth and the number of viral variants recorded in UDS. gp41 and C2V3 sequences strains after four years of ART demonstrated significant increases in viral genetic divergence from the most recent common ancestor sequence as compared to baseline variants from the same individual (p=0.0003 and p<0.0001 respectively). Viral divergence values exhibited trend to negative correlations with the CD4/CD8 ratio (p=0.07 and 0.09). No difference was observed in viral diversity between time points. Compartmentalization analyses indicated the presence of distinct virus populations emerging at each time point in 54% individuals based on both tree topologies and pairwise distance analysis tests to gp41 and in 50% of individual in C2V3. Root-to-tip analyses yielded R2 values ranging from 0.01 to 0.96 in both regions, indicating high correlation between genetic divergence and time and therefore viral evolution. Conclusion: Ongoing viral genetic evolution was detected in the majority of individuals on continuous ART. These results suggest that current ART regimens do not completely suppress viral replication. Residual replicating virus may replenish the proviral reservoir and sustain inflammatory responses, perhaps especially in sanctuaries.